Factors associated with the management of people affected by disabilities in communities endemic to skin-related neglected tropical diseases in Benin and Côte d’Ivoire - Tossou, Yévèdo Borel; Gbaguidi, Fifamin Noël Christelle; Agbo, Sonagnon Inès Elvire; Zanvo, Sètondji Diane Edwige; Codjo-Seignon, Karine Lucrèce Marie; Biaka, Paule Héléna; Guedou, Fernand Aimé; Kouadio, Kouakou Jerôme; Anagonou, Sèdjro Gimatal Esaï; Mignanwande, Franck Zinsou; Djossou, Parfait; Yemadje, Brunelle Vanessa; et al. (Frontiers in Tropical Diseases, 2025)
IntroductionHealthcare systems and social services in developing countries are often ill-equipped to provide comprehensive care for people with disabilities (PWDs). As a result, the quality of life for PWD frequently deteriorates. Comprehensive health care includes five key components: access to diagnosis, treatment, rehabilitation, psychosocial support, and prevention with follow-up. This study aimed to document those segments of the disabled population and factors most associated with inadequate care in regions of Benin and Côte d’Ivoire endemic to neglected tropical diseases (NTDs).MethodsAn exploratory cross-sectional study of PWD was conducted in 2022 in Benin and Côte d’Ivoire, using a combination of quantitative and qualitative approaches. The sample included 841 PWD, 29 caregivers, and 51 family members. Disability management was evaluated using a scoring system ranging from 0 to 5, classifying management into three categories: good management (scores of 4-5), inadequate management (scores of 1-3), and no management (score of 0). Quantitative data were analyzed using SPSS version 25.5, with a p-value of <5% considered statistically significant. Open-ended interviews were carried out with a subsample of PWD, family members, and caretakers to provide further insights into what forms of care were and were not being provided.ResultsAmong PWD, 98 (11.6%) experienced disability associated with skin-related neglected tropical diseases skin-NTDs [apply throughout]. Of the total, 158 (18.8%) received good management, 532 (63.3%) inadequate management, and 151 (18.0%) no management at all. The median age of the sample was 38 years (22; 52), and the male-to-female sex ratio was 1.45. The key factors associated with the quality of disability management (expressed as odds ratios [OR] with 95% confidence intervals [CI] and p-values) were: age 30 to 44 years (OR 0.29 [0.16−0.54], p<0.000), occupation—saleswoman/housewife (OR 0.32 [0.12−0.81], p=0.017), farmer (OR 0.30 [0.16−0.59], p=0.000), other occupations (OR 0.42 [0.18−0.96]), monthly income over 76 euros (OR 0.41 [0.23−0.74], p=0.003), and cause of disability, specifically skin-NTDs (OR 2.15 [1.13−4.09], p=0.000). The interviews highlighted the need for medical interventions, social and economic support.ConclusionComprehensive and sustainable interventions are needed to improve the well being of people affected by disabilities. These need to be built into public health programs for skin-NTDs.